Mycobacterium tuberculosis Rv2617c is involved in stress response and phage infection resistance - Liadrine Moukendza Koundi; Ulrich Aymard Ekomi Moure; Funmilayo Grâce Boni; Insaf Hamdi; Lin Fan; Jianping Xie (Heliyon, 2024)
Mycobacterium tuberculosis (M. tuberculosis) is the pathogen of human tuberculosis (TB). Resistance to numerous in vivo stresses, including oxidative stress, is determinant for M. tuberculosis intracellular survival, and understanding associated mechanisms is crucial for developing new therapeutic strategies. M. tuberculosis Rv2617c has been associated with oxidative stress response when interacting with other proteins in M. tuberculosis; however, its functional promiscuity and underlying molecular mechanisms remain elusive. In this study, we investigated the phenotypic changes of Mycobacterium smegmatis (M. smegmatis) expressing Rv2617c (Ms_Rv2617c) and its behavior in the presence of various in vitro stresses and phage infections. We found that Rv2617c conferred resistance to SDS and diamide while sensitizing M. smegmatis to oxidative stress (H2O2) and altered mycobacterial phenotypic properties (single-cell clone and motility), suggestive of reprogrammed mycobacterial cell wall lipid contents exemplified by increased cell wall permeability. Interestingly, we also found that Rv2617c promoted M. smegmatis resistance to infection by phages (SWU1, SWU2, D29, and TM4) and kept phage TM4 from destroying mycobacterial biofilms. Our findings provide new insights into the role of Rv2617c in resistance to oxide and acid stresses and report for the first time on its role in phage resistance in Mycobacterium.